Human papillomavirus viral load in predicting high-grade CIN in women with cervical smears showing only atypical squamous cells or low-grade squamous intraepithelial lesion - Santos, André Luis Ferreira; Derchain, Sophie Françoise Mauricette; Martins, Marcos Roberto; Sarian, Luís Otávio Zanatta; Martinez, Edson Zangiacome; Syrjänen, Kari Juhani (São Paulo Medical Journal, 2003)
CONTEXT: Human papillomavirus (HPV) viral load may have an important role in predicting high-grade cervical intraepithelial neoplasia (CIN) in women with cervical smears showing atypical squamous cells or LSIL. OBJECTIVE: To determine whether the assessment of the viral load of high-risk HPV DNA is useful in predicting the detection of high-grade cervical intraepithelial neoplasia (CIN2 and 3) in women referred because of cervical smears showing only atypical squamous cells or LSIL. TYPE OF STUDY: Cross-sectional SETTING: Colposcopy Clinic in a University hospital. METHODS: A series of 119 women referred because of atypical squamous cells or LSIL between August 2000 and April 2001 were included. All women were subjected to a new cervical smear, HPV testing for the high-risk types using hybrid capture II (HCII), viral load measurement in relative light units (RLU) and colposcopy, with cervical biopsies (n = 97). Cervical lesions were graded using the CIN classification. RESULTS: Cervical biopsies revealed CIN2 or CIN3 in 11% of the cases, equally among women referred because of atypical squamous cells or LSIL. The HCII test was positive in 16% of women with atypical squamous cells and 52% of those with LSIL (OR = 5.8; 95% CI 1.4 to 26.7). There was strong correlation between CIN2 or CIN3 and positivity for HPV DNA when this group was compared with women with only CIN1 or normal cervix (OR = 7.8; 95% CI 1.5 to 53.4). In ROC analysis for HCII in diagnosing CIN2 and CIN3, the area under the ROC curve was 0.784, and the viral load cutoff point of 10.0 RLU/cutoff presented 77% sensitivity and 73% specificity. Second cytology showing at least atypical squamous cells did not accurately detect CIN2 or CIN3 (OR = 6.4; 95% CI 1.0 to 50.9). The sensitivities of the second cervical smear and HCII were similar, although the specificity of HCII was significantly higher than the second cervical smear. CONCLUSIONS: The viral load of high-risk HPV types was significantly associated with the diagnosis of CIN2 or CIN3 in women referred because of atypical squamous cells and LSIL abnormalities in their cervical smear.